Advanced alternative liquid fuels: For climate protection in the global raw materials change [Position paper of the ProcessNet Working Group“Alternative Liquid and Gaseous Fuels”] - Thomas Willner and Anika Sievers (2018)
Initiative von DECHEMA und VDI-GVC